(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-4-166-181 Abstract. The article considers free dictation as one of the most effective practical methods for the formation of foreign students’ skills in perceiving spoken speech and developing writing skills. The relevance of the research is due to the methodological potential of free dictation, which, from the authors’ point of view, is not fully realized when learning Russian in a foreign-speaking audience. The authors have innovatively and systematically comprehended the criteria for selecting texts for free dictation, built a technology for conducting free dictation, and proposed techniques for working on free dictation based on the text “Modern Cities of the Volga region”. Key words: Russian as a foreign language, free dictation, text selection criteria, speech skills, spelling skills, supporting words